SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENYULUH PERTANIAN MENGGUNAKAN METODE ANALITYCHAL HIERARCHY PROCESS - Alter Lasarudin (Jurnal Ilmu Komputer (JUIK), 2021)
This research was done in Implementing Agency for Agricultural Extension of Fisheries and Forestry Gorontalo City. This research purpose is to design and implementing a Decision Support System to determine agricultural extension agents at the Fishery and Forestry Extension Implementing Agency (BP4K) of Gorontalo City. Researcher will using a multicriteria support decision system named Analytical Hierarchy Process (AHP).With sub-criteria: credit score (K1), duration of promotion (K2), agricultural extension preparation activities (K3), Agricultural extension activities (K4), evaluation activities and agricultural extension reporting in the last 3 years (K5) agriculture in the last 3 years (K6), Professional development activities in the last 3 years (K7), Acquired awards / tandajasa (K8).Based on the results of processing with Analytical Hierarchy Process method is quite effective in accelerating the decision-making process by solving the problem into its parts.